Sosialisasi Permainan Outbond Pada Pengunjung Wisata Botumotolioluwo Desa Longalo Kecamatan Bulango Utara - Isnanto, Juni; Amri, Muhammad Faisal Lutfi; Podungge, Risna; Ilham, Al; Kadir, Sulasikin Sahdi; Ikhsan, Haerul; Syam, Asry (Universitas Negeri Gorontalo, 2023)
Longalo Village has many famous tourist attractions and is visited by many tourists, both nearby tourists, and tourists from outside Longalo Village. Many tourists who visit want to enjoy the beautiful natural scenery of Longalo Village. seeing the development of the current irregular lifestyle, especially in urban areas which are always faced with traffic jams, pollution, and piling up of work, this makes it boring so that it requires activities such as outbound tours that can refresh tourists. The stage of implementing the outbound game socialization service for Botumotolioluwo tourism visitors, Longalo Village, North Bulango District, namely; (1) Surveying to identify environmental conditions in detail, especially for the suitability of implementing program planning socialization; (2) Planning the place for socialization activities; (3) Form a team for the implementation of socialization; (4) Evaluate the results of the socialization of knowledge and safety awareness program planning to tourist visitors. The results of the socialization of outbound games for Botumotolioluwo tourism visitors, Longalo Village, North Bulango District; (1) Planning the socialization program for the implementation of the program; (2) Implementation of the socialization program in the form of outbound games; (3) Evaluation of the outbound game outreach program to visitors.